(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Study of anatomical and morphological characters of interspecific hybrids F1 and starting diploid plants lavender showed that hybrids have significant differences on a number of indicators. This article provides an anatomical and morphological description of the cross section of leaf Lavandula latifolia Medic. (2n, 4n), Lavandula angustifolia Mill. (2n, 4x) and interspecific hybrids containing one parent species genome. Anatomical study of leaf structure of interspecific hybrids showed that the leaf along with their acquired xeromorphic signs of Lavandula latifolia mesomorphic signs of Lavandula angustifolia. F1 hybrids have been a shift from xeromorphic signs to kseromezomorfed. The relationship between the anatomical features of leaves of interspecific hybrids with their productivity, which can be used in genetic and breeding work with lavender is shown.